Eisenmenger syndrome associated with uncorrected open ductus arteriosus - Yu. P. Gabchenko; E. A. Kruchinina; M. Yu. Ishekova; I. V. Petchina; S. P. Lomteva; L. A. Galashevskaya (Лечащий Врач)
Background. Eisenmenger syndrome is the terminal stage of severe shunt disease, which unites all systemic-pulmonary shunts. It is characterized by an increase in pulmonary vascular resistance, which ultimately leads to severe pulmonary arterial hypertension and is the result of a reverse progressive right-to-left shunt or bidirectional ejection of blood. The syndrome is an urgent problem in modern cardiology due to the occurrence of hypoxia and cyanosis, which inevitably lead to multiple complications – secondary erythrocytosis, hemoptysis, celebrovascular disorders, arrhythmias and right ventricular heart failure.Objective. The purpose of the work is to evaluate and describe the complex course of Eisenmenger syndrome in a patient with an uncorrected patent ductus arteriosus.Materials and methods. The work used examination data of a patient (68-year-old woman) who was being treated at the Arkhangelsk Regional Clinical Hospital. Since in our case specific therapy of pulmonary arterial hypertension is difficult for the patient, treatment is carried out in accordance with current recommendations for the management of patients with chronic heart failure with reduced left ventricular ejection fraction.Conclusion. This clinical case illustrates the complexity of managing patients with uncorrected open ductus syndrome with Eisenmenger syndrome, when surgery is not indicated, and the goal of treatment is to reduce pulmonary arterial hypertension and prevent complications.